Physico-chemical characterisation, cytotoxic activity, and biocompatibility studies of tamoxifen-loaded solid lipid nanoparticles prepared via a temperature-modulated solidification method. (September 2014) - Lakkadwala, Sushant; Nguyen, Sanko; Lawrence, Joseph; Nauli, Surya M.; Nesamony, Jerry
Abstract Context: Solid lipid nanoparticles (SLNs) can efficiently and efficaciously incorporate anti-cancer agents. Objective: To prepare and characterise tamoxifen (TAM)-loaded SLNs. Materials and methods: Glyceryl monostearate, Tween-80, and trehalose were used in SLNs. SLNs were tested via dynamic light scattering (DLS), transmission electron microscopy (TEM), differential scanning calorimetry (DSC), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR). Results: Characterisation studies revealed SLNs of about 540 nm with a negative surface charge and confirmed the entrapment of TAM in the SLNs. The entrapment efficiency was estimated to be 60%. Discussion: The in vitro drug release profile demonstrated a gradual increase followed by a release plateau for several days. A drug concentration-dependent increase in cytotoxic activity was observed when the SLNs were evaluated in cell cultures. Conclusion: Biocompatible and stable lyophilised SLNs were successfully prepared and found to possess properties that may be utilised in an anti-cancer drug delivery system.